Applying Andragogy to an Outdoor Science Education Event. Issue 1 (2nd January 2019) - Remenick, Lauren; Goralnik, Lissy
Abstract: Andragogy provides a framework for how adults learn, and contemporary researchers have explored its validity and usefulness in varied contexts. This article joins the discussion by examining andragogy in an as-yet-unstudied setting—an outdoor science education event (HJA Day). In this mixed-methods study, we examine how andragogy applies to HJA Day at the H.J. Andrews Experimental Forest in the Oregon Cascades. HJA Day reflects many aspects of andragogy, with some inconsistencies. For example, many participants preferred learning sessions applicable to their work or personal interests, reflecting the assumption that adults prefer learning content with strong personal relevance. However, some participants attended sessions to be with their friends or to experience a specific learning style, demonstrating a diversion from the andragogical model. Overall, our results affirm the relevance of andragogy for adult field-based science outreach and offer context-specific suggestions for the use of andragogy in outdoor science education.